Identificação e caracterização da infecção por Streptococcus agalactiae em rãs-touro (Lithobates catesbeianus) - Paiva, Vinícius Vieira de (2021)
Brazilian frog culture shows a big importance in world scenario, in adition to being one of the biggest productors, it also stands out for the level of technification. Intensive cultivation in the country allows a large production in small confined spaces, especially when using the flooded system, however the risk of proliferation of infectious diseases also increases considerably. Streptococcus agalactiae causes outbreaks with high mortality in different aquatic species, including Nile tilapia (Oreochromis niloticus), another species of great importance in Brazilian scenario. Between 2018 and 2019 many Streptococcus agalactiae outberaks happened on the aquaculture sector of Universidade Federal de Uberlândia, with a 55% mortality rate in animals in the stage of termination, the study continues with the identification of Streptococcus agalactiae isolates and with the characterization of the disease that occurred in the outbreaks.